Самосогласованная теория эффекта Смита-Парселла на гармониках частоты ЛОВ в двухрежимном генераторе О-типа - Одаренко, Е. Н.; Шматько, А. А.; Юдинцев, П. В. (Weber Co., 2010)
The non-linear theory of Smith-Purcell effect on harmonics of BWO frequency taking into account the two-mode interaction – self-consistent BWO mode and the distributed parametric mode of the diffraction radiation on harmonics of BWO frequency is developed. On the basis of the numerical solution of the self-consistent equations set the existence of the BWO mode of oscillations and parametric type amplification of the diffraction radiation on BWO harmonics is shown.
Keywords: эффект Смита-Парселла; двухрежимный прибор О-типа; нелинейная теория